KAJIAN PENDAHULUAN KELAYAKAN PENERAPAN INSTALASI PENGOLAHAN AIR LIMBAH DOMESTIK SECARA KOMUNAL DI PERMUKIMAN KOTA BOGOR - Rifai, Agus; Nugroho, Rudi (Center for Environmental Technology, 2007)
A preliminary assessment of an application of sewerage system with Upflow Anaerobic Sludge Blanket (UASB) and Down flow Hanging Sponge (DHS) technology was conducted inNorth Bogor. The Problem which often emerge in management of domestic wastewater is the limited land area and fund to built and operate a wastewater treatment facility. To overcome such problem, it is needed to develop a cheap wastewater treatment technology with high efficiency, easy to operate and also should be compact. The combination technology of UASB and DHS is proposed as an economic wastewater treatment whichÃ‚Â easy to handling. Therefore, to make sure that the technology is feasible or not to be built inNorth Bogor, there is need the preliminary assessment. The assessment was conducted through a survey of technical and social economic aspect. The results show that sewerage system using UASB and DHS technology is feasible.Ã‚Â Key word: domestic wastewater, upflow anaerobik sludge blanket, downflow hanging sponge, preliminary assessment.